THE EFFECT OF USING VISUAL, AUDITORY, KINESTHETIC (VAK) LEARNING MODEL ON STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT - Halimatun Husna Rambe and Zainuddin (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study deals with the applications of Visual, Auditory, Kinesthetic (VAK) Learning Model on Students’ Achievement in Writing Recount Text. It was conducted by using experimental research. The objective of the study was to find out whether VAK learning model significantly effected the students’ achievement in writing recount text. This study was conducted to 2013/2014 the eighth grade of SMP N. 1 Tg.Morawa, which consisted of 324 students in nine classess. The sample was divided into two groups: experimental and control groups. The instrument used to collect the data was writing test. It was found that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group at the level of significance µ = 0.05 with the degree of freedom (df) 70, t-observed value 2.39 > t-table value 1.994. It means that Visual, Auditory, Kinesthetic (VAK) Learning Model has a significant effect on students’ achievement in Writing Recount Text